Peran Penting Inflamasom NLRP3 pada Aterosklerosis - Sukmawati, Dewi (Jurnal Penyakit Dalam Indonesia, 2023)
Cardiovascular diseases (CVDs) still contribute as the main cause of mortality and premature mortality worldwide. In Indonesia, CVDs contribute to 35% of the main cause of death in non-communicable diseases followed by diabetes at 6%. The ischemic heart disease and acute ischemic stroke is the main cause of death in Indonesia due to atherosclerosis. Atherosclerosis is a multifactorial cause, with chronic inflammation which causes myocardial infarction and acute ischemic stroke. Research demonstrated that one of the underlying mechanisms of atherosclerosis is inflammation. The current research suggested that inflammation could activate a complex of cytosol proteins, namely nucleotide-binding oligomerization domain-like receptor family pyrin domain containing 3 (NLRP3) inflammasome. The NLRP3 inflammasome is known as a protein sensor as a response to danger signals known as pathogen-associated molecular patterns (PAMPs) or damage/danger-associated molecular patterns (DAMPs). The NLRP3 inflammasome will convert the pro-IL1β and pro-IL-18 into their mature forms which initiates the cell death (pyroptosis) through the cleavage of Caspase-1. This NLRP3 inflammasome has a central role in the initiation and progression of atherosclerosis by affecting the sequences of its cellular and molecular targets. To date, several small molecules and drugs have been identified as NLRP3 inflammasome inhibitory pathways and potential therapeutic agents for atherosclerosis. In this review, we will discuss further the structure of NLRP3 inflammasome and its roles in atherosclerosis, and the potential candidates of the small molecules and drugs targeted in the inflammasome pathway.